Perancangan Panti Sosial Tresna Werdha Berdasarkan Kebutuhan dan Pola Perilaku Pengguna - Chairun Annisa; Marisa, Amy (Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
Life expectancy in Indonesia has significantly increased. The 2010 census shows that the Indonesian population has a life expectancy of up to 70.7 years. As for Medan, life expectancy increased to 73.14 in 2020, with 129,063 older people. The number of residents is considered unbalanced with the number of available nursing homes, and there are still few nursing homes with adequate facilities. Nursing homes are also often seen as an act of alienation for the elderly; they are considered harmful. Therefore, nursing homes will implement a behavioural architecture, which is an architecture that, in its application, always includes considerations of user behaviour in its design. This research aims to make a nursing home a facility that can make the elderly comfortable and safe by considering their needs and behaviour patterns. The method used is a qualitative approach in which data is collected through observation, field surveys, literature studies, and comparative studies. The results show that the design of the nursing home must support and meet the needs of the elderly, who tend to require their territory, need an area with a good view, a bright and quiet environment, and can socialize easily. The results of this study can be used as a basis for designing nursing homes in the future.